A delayed diagnosis of lymphatic filariasis in a returned traveller from the Philippines - Drewett, George P; Pourhadi, Hedayat; Kahn, Jordan; Tio, Shio Yen; Aboltins, Craig (Communicable Diseases Intelligence, 2025)
A 71-year-old Australian-born man with previous extended travel to the Philippines presented with bilateral lymphoedema, fevers and rigors. Examination of a nocturnal blood film revealed microfilariae of Wuchereria bancrofti, confirming a diagnosis of Bancroftian filariasis. This case highlights the challenges of diagnosing and managing lymphatic filariasis in non-endemic regions.